Effectiveness of Information and Communication Technologies in Promoting and Disseminating Information to Users at the Museum and House of Culture, Dar es Salaam, Tanzania - Fred, Sophia; Nawe, J (University of Dar es Salaam Library Journal, 2017)
This study mainly investigated the effectiveness of Information and Communication Technologies in promoting and disseminating information to users at the Museum and House of Culture (MHC). Spesifically, the study sought to identify information and communication channels used, examine the application of ICT in online and onsite museum services and the patterns of ICT use, and to determine the challenges faced in applying ICT in promoting and disseminating information to the users. The sample size consisted of 72 respondents (48 staf fand 24 museum users). Data for this study were collected using documentary review, questionnaires, interviews, focus group discussion and observation. Whereas quantitative data were analysed using SPSS qualitative data were subjected to content analysis. The study findings revealed that MHC uses various channels of communication and that electronic and computerised communication channels were preferred by the majority of the respondents. The challenges to effective utilisation of ICT at the Museum included inadequate skills, inadequate funds, technological obsolescence and technophobia among staff. The study concludes that, although MHC uses various channels of communication and different ICTs in its operations, communication links at the MHC have a lot of weaknesses and challenges. Thus, the study recommends the formulation of the Museum Information and ICT Policy to have in place a staff development plan in addition to increasing public awareness on museum potentiality.